PENGARUH MODEL NUMBERED HEADS TOGETHER TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Suci Istiqamah (Jurnal Edukasi dan Penelitian Matematika, 2018)
Understanding of mathematical concepts is a basic skill that must be possessed by learner, because understanding of good concepts will be the basic provision for learners to reach next ability. But in fact, students’ understanding mathematical concepts of class VIII SMP Negeri 15 Padang still low. One of the solutions offered is cooperative learning model type Numbered Heads Together. Purpose of this study is the students’ understanding mathematical concepts who learn to use cooperative learning model Numbered Heads Together better than the understanding of mathematical concepts of learners who learn with conventional learning of class VIII SMP Negeri 15 Padang. Type of research is a quasi experimental research with the design of Static Group Design. Results showed that ability to understanding the mathematical concepts of learners by applying cooperative learning model type Numbered Heads Together better than the understanding of mathematical of learners who learn with conventional learning.Keywords – conventional learning, numbered heads together, understanding of mathematical concept